Neuropeptide Y-like immunoreactivity in rat cranial parasympathetic neurons: coexistence with vasoactive intestinal peptide and choline acetyltransferase. - Leblanc, G G (1987)
Neuropeptide Y (NPY) is widely distributed in the sympathetic nervous system, where it is colocalized with norepinephrine. We report here that NPY-immunoreactive neurons are also abundant in three cranial parasympathetic ganglia, the otic, sphenopalatine, and ciliary, in the rat. High-performance liquid chromatographic analysis of the immunoreactive material present in the otic ganglion indicates that this material is very similar to porcine NPY and indistinguishable from the NPY-like immunoreactivity present in rat sympathetic neurons. These findings raise the possibility that NPY acts as a neuromodulator in the parasympathetic as well as the sympathetic nervous system. In contrast to what has been observed for sympathetic neurons, NPY-immunoreactive neurons in cranial parasympathetic ganglia do not contain detectable catecholamines or tyrosine hydroxylase (EC 1.14.16.2) immunoreactivity, and many do contain immunoreactivity for vasoactive intestinal peptide and/or choline acetyltransferase (EC 2.3.1.6). These findings suggest that there is no simple rule governing coexpression of NPY with norepinephrine, acetylcholine, or vasoactive intestinal peptide in autonomic neurons. Further, while functional studies have indicated that NPY exerts actions on the peripheral vasculature which are antagonistic to those of acetylcholine and vasoactive intestinal peptide, the present results raise the possibility that these three substances may have complementary effects on other target tissues.